Characteristics of 1000 Femur Fractures in the Dog and Cat - Braden, T. D.; Eicker, S. W.; Abdinoor, D.; Prieur, W. D. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
A fracture documentation study of the femur in dogs and cats was developed. It consists of frequency of type of animal involved, the type of fracture involved, and the type of repair carried out. Specifically, the data documented are: date, leg, patient number, practice number, surgeon number, sex, species, age, weight, amount overweight, fracture site, skin condition, fragment number, days trauma to surgery, Salter type, management, presurgical complications, primary fixation, secondary fixation, graft, cerclage wire, cerclage method, screw size, Kirschner wire size, pin size, plate, pins (Kirschner apparatus), bars (Kirschner apparatus). This data was collected over a five-year period from 79 surgeons in private and university practice in 10 different countries.One thousand femur fractures were documented in this retrospective study. The type of animals and type of fractures are reported herewith. Also the type of fixation is reported. This is the most comprehensive femur fracture study reported to date.
Keywords: Fracture; documentation; femur; characteristics